The MIND Dietary Pattern Is Selectively Related to Cognitive Processing Speed. (14th June 2022) - Holthaus, Tori; Kashi, Monica; Cannavale, Corinne; Edwards, Caitlyn; Aguiñaga, Susan; Walk, Anne; Burd, Nicholas; Holscher, Hannah; Khan, Naiman
Abstract: Objectives: Given that previous research has disproportionately focused on individual nutrients, knowledge of diet patterns and cognitive health is limited. Thus, we investigated the relationship between different diet indices (Mediterranean, Dietary Approaches to Stop Hypertension [DASH], Healthy-Eating-Index-2015 [HEI-2015], and Mediterranean-DASH Intervention for Neurodegenerative Delay [MIND]) and attentional inhibition and neuroelectric function. Methods: Adults aged 34.1 ± 6.0 years old (N = 207) completed the Dietary History Questionnaire II (DHQII, Past Year and Past Month with Portion Size) to assess adherence to different diet indices. Attentional inhibition was assessed using a modified Eriksen Flanker task while event-related potentials (ERPs) were recorded. The amplitude and latency of the P3 ERP component were used to index attentional resource allocation and information processing speed, respectively. Stepwise linear regression modeling was used to assess the influence of each dietary index on behavioral performance and neuroelectric function following adjustment for significant covariates (e.g., age, sex, intelligence quotient, and body mass index). Results: Greater adherence to the MIND diet was associated with an earlier incongruent P3 peak latency ( ∆R 2  = 0.02, β = −0.14, p  = 0.04) but not congruent peak latency (∆ R 2  = 0.02, β = −0.12, p  = 0.07). Adherence to the Mediterranean, DASH, and HEI-2015 patterns was not correlated with P3 latency ( p  > 0.05). No associations were observed between the diet indices and attentional inhibition at the behavioral level (i.e., accuracy or reaction time) or P3 amplitude (all p's  > 0.05). Conclusions:  Greater adherence to the MIND diet was selectively related to faster information processing speed. This relationship was only evident during incongruent trials, suggesting that the influence of greater MIND diet adherence is particularly beneficial when upregulation of cognitive control is required. Future MIND diet intervention trials are warranted to help inform dietary recommendations for healthy cognitive aging. Funding Sources: This work was funded by the Department of Kinesiology and Community Health at the University of Illinois, Division of Nutritional Sciences, and Hass Avocado Board.